A Study on Determination of Prescription Writing Errors in out Patient Department of Medicine in a Teaching Hospital - A, Ather; P, Neelkantreddy; G, Anand; G, Manjunath; J, Vishwanath; M, Riyaz (Indian Journal of Pharmacy Practice)
Introduction: Prescription is an order for medication issued by a properly licensed medical practitioner to the pharmacist. The prescription should be clearly written, free from writing errors, and fulfil the legal requirements. The prescription writing errors leads to the medication errors, which in turn leads to failure of therapeutic goals. Objective: Anine month prospective study was carried out to determine the prescription writing errors at a Teaching Hospital. Results: Atotal of 290 prescriptions were randomly collected from out patients visiting the study site, and analyzed. Among them 635 errors of omission related to prescribers and 184 errors of omission related to the drugs with an average of 2.18 and 0.63 errors per prescription respectively. The errors of omission related to prescribers were due to failure to mention signature of prescriber 27(9.31%) followed by diagnosis 27(9.31%), prescribers name 261(90%), patients weight 290(100%) and 30(10.34%) were due to illegible hand writing. The errors of omission related to drugs were due to failure to mention frequency 13(4.4%) followed by quantity to supply 18(6.20%), dosage form 23(7.93%), strength 41(14.13%) and duration/no of doses 89(30.68%). An 82 errors of commission were due to wrong strength 12(4.13%) followed by wrong drug name 19(6.55%), wrong dosage form 23 (7.93%) and drug-drug interactions 28(9.65%). Conclusion: The study results indicate that errors in prescription writing were significant at the study site, which highlights the need of conducting the educational programs to improve the prescription writing skills of the prescribers.
Keywords: Prescription; errors; omission; commission